The Use of Assessment of Chronic Illness Care Technology to Evaluate the Institutional Capacity for HIV/AIDS Management - Silva, Andressa Wanneska Martins da; Meiners, Micheline Marie Milward de Azevedo; Noronha, Elza Ferreira; Toledo, Maria Inês de (Frontiers in Pharmacology, 2019)
The effectiveness of antiretroviral therapy has rendered HIV infection a manageable chronic condition. Currently, the health systems face the challenge of adopting organizational healthcare models capable of ensuring the delivery of comprehensive care. The Chronic Care Model has been reported for its effectiveness, particularly in terms of delivery system design. In this study, the Assessment of Chronic Illness Care (ACIC) questionnaire, a soft technology widely used for other chronic conditions, was employed on a teaching hospital to evaluate healthcare provided to people living with HIV/AIDS. The ACIC technology is a self-explanatory instrument which diagnoses, among the six components of the Chronic Care Model Framework, areas for quality improvements, indicating at the same time, intervention strategies and achievements. These components are healthcare network organization, delivery system design, self-management support, decision support, clinical information systems and community. From May to October 2014, the tool was applied to the multidisciplinary teamwork at the points of care identified, as well as to the hospital management board. Respondents broadly rated care as basic. A pronounced contrast was observed from evaluation by management board and health professional staff in some components like organization of healthcare and clinical information system. The self-management support and delivery system design were the components best evaluated by the multidisciplinary team. Combined with the array of services offered, the entry points available at the hospital can ensure healthcare comprehensiveness. However, some gaps were detected, precluding the delivery of an effective care. The ACIC was considered an adequate technology to provide knowledge of the gaps, to promote productive discussions and reflections within teams and to indicate actions to achieve improvements on healthcare for people living with HIV/AIDS.